The Effects of Applying Social Responsibility on The Economic Enterprise: Case Study PEUGEOT - Reggami , Mohamed; bouchenkir , Imen (Finance and Business Economies Review, 2023)
The economic enterprise is concerned with determining what Social responsibility is and its importance for enterprises, and the various theories related to it, and then raise the main problem which is: What are the various effects of applying social responsibility in economic enterprise?, the study concluded that the enterprise should continue to regulate social responsibility voluntarily and in accordance with each country, but not inconsistent with the enterprise’s doctrine, which improves her image and that with the aim of obtaining greater financial returns.